A systematic assessment of the concept and practice of public-private mix for tuberculosis care and control - Malmborg Rasmus; Mann Gillian; Squire S (BMC, 2011)
Abstract Introduction The STOP TB Partnership aims to improve global tuberculosis (TB) control through expanding access to the directly observed treatment short course (DOTS) strategy. One approach to this is 'Engaging all Care Providers', which evolved from 'Public-Private Mix (PPM) DOTS'. The overall aim of this study was to systematically assess whether and to what degree the STOP TB Partnership's four global objectives of engaging all care providers are met through existing PPM interventions. These four objectives are; 1) Increase TB case detection; 2) Improve TB treatment outcomes; 3) Enhance access and equity; 4) Reduce financial burden on patients. The specific objectives of this assessment were to 1) Understand what PPM means to the STOP TB Partnership's PPM Subgroup and to National Tuberculosis Programme managers; 2) Scope the nature of existing country-level PPM interventions and 3) Review PPM practice against the global PPM objectives. Methods We undertook a systematic, multi-facetted assessment. The methods included interviews with National Tuberculosis Programme managers from high burden countries, clarification of key issues with the STOP TB Partnership PPM secretariat and a review of publicly accessible reports and published articles on PPM projects. Both the literature review and interviews with the National Tuberculosis Programme managers yielded data on project characteristics; PPM models at country level; National Tuberculosis Programme partners; and mechanisms for engagement. Matrices were developed from the literature review and the interviews to show the relationship between services and service providers for different PPM projects. Data from the literature were assessed against each of the four global PPM objectives. Results Twelve National Tuberculosis Programme managers from high burden countries were interviewed about the scope of PPM partnerships. Understanding of PPM and types of engaged providers varied considerably; 'private-for-profit qualified clinical providers' were the dominant category. The literature review yielded information on 22 projects in which 'private-for-profit qualified clinical providers' were again the dominant category. The contributions made by 'private-for-profit qualified clinical providers' and 'Non Governmental Organisation qualified clinical providers', were assessed against the four global PPM objectives. Reporting on tuberculosis case detection and treatment outcomes was generally good and demonstrated important PPM contributions in these areas. Reporting on equity, access and reduced patient costs was often lacking or inconclusive. Conclusions PPM has improved case detection and treatment outcomes among patients seeking care with private providers. Evidence on reducing patient costs is inconclusive, and there is scope for increasing equity in access to care by systematically engaging those providers who are the primary agents for poor people seeking health care. Guidelines outlining which types of providers best contribute to achieving the four global objectives, along with the resources required by National Tuberculosis Programs for such engagement is needed.